A MORPHOLOGICAL ANALYSIS OF TERMS USED IN GENSHIN IMPACT COMMUNITY ON HOYOLAB - Dian Zahira Azeva; Eka Wilany; Safnidar Siahaan (Lire Journal (Journal of Linguistics and Literature), 2026)
This study analyzed morphological processes in terms used by the Genshin Impact community on HoYoLAB, where English serves as the lingua franca in communication between players. Using a qualitative descriptive approach, data was collected from user posts and comments and analyzed using morphological theory. The results showed that composition is the dominant process, followed by compounding, clipping, initialisms, abbreviations, and derivations, which are primarily used to support efficient communication in online discussions, while borrowings are less common and mainly associated with narrative and tradition-related contexts. This study highlights the role of morphological processes in shaping community-specific terminology and reflects the dynamics of language use in digital gaming communities.